2017
DOI: 10.3390/met7050166
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modelling of Energy Density and Optimization of the EDM Machining Parameters of Inconel 600

Abstract: Abstract:In this present research work, a new modelling of energy density in EDM (Electrical Discharge Machining) is proposed. Energy density can be defined as the amount of energy needed to get a unit volume of material removed, and for its modelling, the whole EDM process has been taken into account. This new definition lets us quantify the energy density that is being absorbed by the workpiece and the electrode. Results are compared to those obtained by die sinking EDM in an Inconel ® 600 alloy using Cu-C e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…In manufacturing processes, is it quite common for certain technological variables to have a more regular response behavior and, therefore, they can be modeled by methodologies such as RSM, and, on the other hand, there also exist some other technological variables that cannot be adequately modeled using conventional regression techniques. For example, in Reference [61] it is shown that the arithmetic average roughness (Ra) can be approximated by a polynomial regression using RSM, in an EDM process. However, due to the variability of the data, the wear that the electrode (EW) undergoes in this EDM process cannot be adequately modeled by using RSM, and for this reason, in order to adequately model this technological variable, it would be necessary to employ some other technique, for example based on using an ANFIS or an ANN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In manufacturing processes, is it quite common for certain technological variables to have a more regular response behavior and, therefore, they can be modeled by methodologies such as RSM, and, on the other hand, there also exist some other technological variables that cannot be adequately modeled using conventional regression techniques. For example, in Reference [61] it is shown that the arithmetic average roughness (Ra) can be approximated by a polynomial regression using RSM, in an EDM process. However, due to the variability of the data, the wear that the electrode (EW) undergoes in this EDM process cannot be adequately modeled by using RSM, and for this reason, in order to adequately model this technological variable, it would be necessary to employ some other technique, for example based on using an ANFIS or an ANN.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Torres at al. [61] employed a 4 3 factorial DOE for modeling the behavior of the arithmetical mean roughness (Ra), the electrode wear (EW) and the MRR in the EDM machining of an Inconel ® 600 alloy using Cu-C electrodes (Inconel®600 alloy is a registered trademark of the Special Metals Corporation group of Companies). In Lin et al [62] surface roughness in the end-milling process is analyzed as a function of spindle speed, cutting depth, and feed rate and machining vibration by using multiple regression and ANNs and in Karloopia et al [63] cutting speed, depth of cut, and feed are used as independent variables to obtain cutting force and tool wear in Al-Si-TiB2 composites by using linear regression.…”
Section: State Of the Artmentioning
confidence: 99%
“…The conductivity of the deionized water was 0.1 µS•cm −1 ; electric voltage V o = 270 V; and current intensity I e = 0.05 A. The frequency of the working impulses was f w = 0.2 MHz [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…They suggested mathematical models for the determination of the optimal combination of significant technological parameters in order to minimize microhardness and total HAZ depth variations of tool steel EN X32CrMoV12-28 after die-sinking EDM with a SF-Cu electrode. Optimization of EDM machining parameters of Inconel 600 was presented in [11]. They analytically modeled the energy density, which is being absorbed by the workpiece and the electrode, and experimentally confirmed that the negative polarity leads to a higher material removal rate, higher electrode wear and higher surface roughness.…”
Section: Introductionmentioning
confidence: 99%